2020
DOI: 10.33448/rsd-v9i3.2399
|View full text |Cite
|
Sign up to set email alerts
|

Atributos físicos e teor de matéria orgânica em área de Cerrado sob diferentes sistemas de cultivo

Abstract: The cultivation of different species promotes positive or negative changes in the chemical, physical or biological properties of the soil. In this context, this work aimed to evaluate the physical attributes of the soil and the organic matter levels in the Cerrado, under different cultivation systems. The treatments evaluated were the Cerrado sensu stricto, Cerrado in regeneration, eucalyptus and sugarcane, used entirely randomized design (DIC), with six repetitions in the ranges of depth 0-10, 10-20 and 20-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Clayey soils require more time for increases in OM to change soil physical properties compared with sandy soils, where small increases in OM result in fast changes (Borges et al, 2020). Serpa et al (2020) observed that management and cover crops produced significant differences in soil physical quality, with the plants that yielded the highest amount of crop residues positively affecting soil physical properties, especially in the topsoil layers.…”
Section: Resultsmentioning
confidence: 99%
“…Clayey soils require more time for increases in OM to change soil physical properties compared with sandy soils, where small increases in OM result in fast changes (Borges et al, 2020). Serpa et al (2020) observed that management and cover crops produced significant differences in soil physical quality, with the plants that yielded the highest amount of crop residues positively affecting soil physical properties, especially in the topsoil layers.…”
Section: Resultsmentioning
confidence: 99%
“…The Cerrado is Brazil's second largest biome, and is also considered a "hotspot" for the conservation of global biodiversity due to the high concentration of endemic species. (Serpa et al 2020) In this sense, this study aimed to analyze the spatial distribution and to identify the diametric and height structures of individuals from populations of Q. parviflora and C. fasciculata and also to know, evaluate and describe the phenological cycle of the two species occurring in a Cerrado fragment in middle of crystalline Caatinga, municipality of Lavras da Mangabeira, southern Ceará state, being the first study involving typical species of Cerrado in Caatinga core area. It is then expected to afford management actions and improve the understanding of the ecological behavior of these species in disjoint environments.…”
Section: Introductionmentioning
confidence: 99%
“…A produção agrícola, pecuária e florestal pode promover reduções significativas na qualidade do solo (Freitas et al, 2020;Serpa et al, 2020). A busca pela sustentabilidade da produção agropecuária e florestal tem se intensificado frente a necessidade da preservação dos recursos naturais e de melhorias em questões sociais e econômicas.…”
Section: Introductionunclassified